Analisis Rasio Profitabilitas Terhadap Harga Saham (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2012-2015) - Fajrina, Nurul; , Kusdiyanto, S.E., M.Si (2017)
This study aims to determine the significant influence profitability ratios to the stock price and to determine which of the variables ROA, ROE, NPM, and EPS have a significant effect on stock prices. The data used in this research is secondary data in the form of quantitative data. The data used in this study were taken from the site www.idx.go.id. Data analysis using profitability ratios that include Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS). Classis assumption test used include normality test, mulicollinearity test, heterocedasticity test, and autocorrelation test. Test hypotheses used include multiple linear regression analysis, t-test, f-test, and test the coefficient of determination (R2). The results showed that in partial ROA (X1), ROE (X2) and EPS (X4) has a significant influence on stock pices (Y), while the NPM (X3) variable no significant effect on stock prices (Y). Simultaneously ROA (X1), ROE (X2) and EPS (X4) has a significant influence on stock prices (Y). Of the four variables studied were ROA (X1), ROE (X2), NPM (X3) and EPS (X4) turn variable EPS (X4) having a value most dominant. Based on the R Square in this study is worth 0.642 (64.2%), which means that of the four variables studied were ROA (X1), ROE (X2), NPM (X3) and EPS (X4) is able to provide an explanation of the stock price variable (Y) amounted to 64.2% and is still influenced by other variables amounted to 35.8%.